MEMS pressure sensor for gait analysis - Nurismaliza Jurami (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this research are ; to design the MEMS pressure sensor by using COMSOL software ; to study the effect of pressure sensor by using two different materials, PZT and ZnO with different thickness sizes of piezoelectric material ; to identify the minimum and maximum pressure for gait application.